Toxicology and digestibility of Chlamydomonas debaryana green algal biomass - Murbach, Timothy S.; Glávits, Róbert; Jayasena, Shyamali; Moghadam Maragheh, Niloofar; Endres, John R.; Hirka, Gábor; Goodman, Richard E.; Vértesi, Adél; Béres, Erzsébet; Pasics Szakonyiné, Ilona (Journal of applied toxicology, 2023)
There is an economic interest, both for food security and for the non‐meat‐eating population, in the development of novel, sustainable sources of high‐quality protein. The green algae Chlamydomonas reinhardtii has already been developed for this purpose, and the closely related species, Chlamydomonas debaryana, is a complementary source that also presents some additional advantages, such as reduced production cost. To determine whether C. debaryana may have a similar safety profile to that of C. reinhardtii, a wild type strain was obtained, designated TS04 after confirmation of its identity, and subjected to a battery of preclinical studies. Genetic toxicity was evaluated using a bacterial reverse mutation test, an in vitro mammalian chromosomal aberration test, and an in vivo mammalian micronucleus test in a mouse model. No genotoxic potential (e.g., mutagenicity and clastogenicity) was observed in these tests under the employed conditions up to maximum recommended concentrations or doses. To assess general toxicity, a 90‐day repeated‐dose oral toxicity study was conducted in rats. No mortality or adverse effects were observed, and no target organs were identified up to the maximum feasible dose, due to solubility, of 4,000 mg/kg bw/day. The no‐observed‐adverse‐effect level was determined as the highest dose tested. A digestibility study in simulated gastric fluid was conducted and determined that TS04 has low allergenic potential, exhibiting rapid digestion of proteins. Due to the negative results of our evaluation, it is reasonable to proceed with further development and additional investigations to contribute towards a safety assessment of the proposed use in food for human consumption. Due to interest in developing the green algae Chlamydomonas debaryana as a source of food protein, a wild type strain was obtained, designated TS04, and subjected to preclinical safety testing. TS04 did not exhibit allergenic potential in a digestibility study or genotoxic potential in a standard battery of tests. A no‐observed‐adverse‐effect level of 4,000 mg/kg bw/day (the highest dose tested) was determined in a 90‐day repeated‐dose oral toxicity study in rats. Based on these results, further evaluation and development are feasible.